Kinopanorama . Kinopanorama . Film Panorama . Кинопанорама - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Discussion on the independence of filmmakers from the state and state evaluation of the morality of the films. Included are segments from the following films: "Tamara Alexandrovna's Husband and Daughter," "Confession. A Chronicle of Alienation," "Black Rose - Emblem of Sorrow," and "Red Rose - Emblem of Love." Series description: A program about films and cinema, broadcasted on Soviet and Russian TV from 1962 to 1995. Until the beginning of the 1970s the program had a live broadcast. Its director was Ksenia Marinina, it editors were N. Kartseva and M. Speranskaia and S. A. Kuznetsov (the chief editor of the editorial office of the Central Television Studio). The ptorgam had a surveying and advertising character. The anchorperson introduced a certain film, told about its creators, shootings, production and distribution, etc. Then the excerpts from this film were demonstrated. Обсуждение независимости кинодеятелей от государственного управления; государственная оценка моральности фильмов. Съемки фильма "Муж и дочь Тамары Александровны", "Исповедь. Хроника отчуждения", "Чёрная роза — эмблема печали, красная роза — эмблема любви". Описание серии: Телевизионная передача о кино. Демонстрировалась на советском и российском телевидении с 1962 по 1995 год. До начала 1970-х передача выходила в прямом эфире. Режиссером программы была Ксения Маринина, редакторами - Н. Карцева, М. Сперанская и С. А. Кузнецов (главный редактор киноредакции Центральной студии телевидения). Телепередача носила обзорный-рекламный характер. Ведущий в студии представлял тот или иной фильм, рассказывал о его создателях, съёмках, особенностях производства и проката и т. д., затем демонстрировались отрывки из фильма.